The Thanksgiving story - Dalgliesh, Alice, 1893-; Sewell, Helen, 1896- (New York : Scribner's, 1988)
A Pilgrim family's struggle to survive in their harsh new homeland culminates in a thanksgiving feast.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Caldecott Medal/Honor
3.9
K-3
Keywords: Pilgrims (New Plymouth Colony) -- Fiction; Thanksgiving Day -- Fiction; Thanksgiving Day -- Fiction; Pilgrims (New England colonists) -- Fiction